Introduzione. Ernesto Balducci: una figura pedagogica di forte attualità - Alessandro Mariani (Studi sulla Formazione)
This contribution aims to introduce the proceedings of the national conference dedicated to “Ernesto Balducci: a pedagogical figure of strong relevance,” which took place one hundred years after his birth (and thirty years after his death) with the purpose of both honoring his memory and scientifically deepening-in an interdisciplinary perspective and through a pluralism of expert voices-both the pedagogical force and the actual relevance of the thought and action of a true master, including in the educational field.